2009
DOI: 10.1111/j.1540-6237.2008.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Competing Social Movements and Local Political Culture: Voting on Ballot Propositions to Ban Same‐Sex Marriage in the U.S. States*

Abstract: This article uses social movement theory to explain variation in local support for proposed constitutional amendments to ban same-sex marriage in 22 states during 2004 and 2006. Copyright (c) 2009 by the Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 22 publications
(33 reference statements)
1
34
0
Order By: Relevance
“…The differences among participants as a function of their socio-demographic groups also followed the predicted direction and thus confirming the construct validity of the Portuguese ATSM Scale version. Only age and educational attainment did not achieve the levels usually found in the literature (e.g., Fleischmann, & Moyer, 2009;Lewis, & Gossett, 2008;Montgomery, & Stewart, 2012;Pearl, & Gallupo, 2007). However, in our opinion, this may be attributed to the relative homogeneity of the present sample as regards these two variables.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The differences among participants as a function of their socio-demographic groups also followed the predicted direction and thus confirming the construct validity of the Portuguese ATSM Scale version. Only age and educational attainment did not achieve the levels usually found in the literature (e.g., Fleischmann, & Moyer, 2009;Lewis, & Gossett, 2008;Montgomery, & Stewart, 2012;Pearl, & Gallupo, 2007). However, in our opinion, this may be attributed to the relative homogeneity of the present sample as regards these two variables.…”
Section: Discussionmentioning
confidence: 69%
“…In other words, the proven effects of religiosity and political orientation in attitudes towards same-sex marriage are to some extent due to the stronger beliefs that religious and right wing people hold about the transcendent nature of the marriage institution. Following previous research on predictors of attitudes towards lesbian and gay men in other countries (e.g., Bessen, & Zicklin, 2007;Fleischmann, & Moyer, 2009;Herek, 2006;Moskowitz et al, 2010), we expect that men (vs. women), with lower (vs. higher) educational levels, married (vs. single, living as married or divorced), religious (vs. nonreligious), embracing a right-wing (vs. left-wing) political ideology, and without (vs.…”
Section: The Attitudes Towards Same-sex Marriage Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Across the literature, gender, age, religious affiliation, religious intensity, education, income, marital status, ethnicity, and contact with gay people have all been suggested as significant sources of variation in attitudes on gay rights issues. In most studies, males, older respondents, Protestants, Catholics, those with greater church attendance, those with less education, lower-income respondents, African Americans, Latinos, married respondents, those from rural areas, Southerners, and those with limited contact with gays and lesbians all demonstrated lower support for same-sex marriage and were more likely to vote for bans (Barth, et al 2009;Baunach 2012;Becker 2012aBecker , 2012bBecker and Scheufele 2009;Brewer 2008;Brumbaugh, et al 2008;Burnett and Salka 2009;Dyck and Pearson-Merkowitz 2012;Egan and Sherrill, 2009;Fleischmann and Moyer 2009;Gaines and Garand 2010;Lewis and Gossett 2008;McKenzie and Rouse 2013;McVeigh and Diaz 2009;Olson et al 2006;Salka and Burnett 2012;Sherkat et al 2010;Sherkat et al 2011). Several of these studies report inconsistent results for some variables including gender, age, income, ethnicity, and marital status.…”
Section: Factors Influencing Opinion On Same-sex Marriagementioning
confidence: 99%
“…Seventy‐six percent of evangelical Christians report that religion is important or very important in their lives and has a strong connection to their political opinions (Green, ). These religious communities have a significant effect on the social and political views of their adherents; recent work has shown that evangelicals display significant opposition to state sanctioning of contentious public issues, including the teaching of evolution (Haider‐Markel and Joslyn, ) and the legalization of same‐sex marriage (Fleischmann and Moyer, ).…”
Section: Theory: Political Determinants Of Family Leave Policymentioning
confidence: 99%